1990
DOI: 10.1007/bf00400203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperglycaemia on sorbitol and myo-inositol contents of cultured embryos: treatment with aldose reductase inhibitor and myo-inositol supplementation

Abstract: To demonstrate the myo-inositol depletion hypothesis in hyperglycaemia-induced embryopathy, rat conceptuses of 9.5 days of gestation in the early head-fold stage were grown in vitro during neural tube formation for 48 h with increasing amounts of glucose. The effects of an aldose reductase inhibitor and the myo-inositol supplementation were also investigated. Sorbitol and myo-inositol contents were measured in separated embryos and extra-embryonic membranes including yolk sac and amnion at the end of culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Homocysteine has been reported to be embryo-toxic during the process of neural tube formation [40][41][42] and is known to increase the reactive oxygen species (ROS) [43]. Although the mechanism of diabetes-induced congenital defects remains unclear, an excess of ROS, increased somatomedin inhibitor, myo-inositol deficiency, increased lipid peroxidation, arachidonic acid deficiency, and altered prostaglandin have been reported to be involved in the pathogenesis of diabetes-induced embryopathy [24,38,[44][45][46]. Especially, the excess of ROS is thought to be particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine has been reported to be embryo-toxic during the process of neural tube formation [40][41][42] and is known to increase the reactive oxygen species (ROS) [43]. Although the mechanism of diabetes-induced congenital defects remains unclear, an excess of ROS, increased somatomedin inhibitor, myo-inositol deficiency, increased lipid peroxidation, arachidonic acid deficiency, and altered prostaglandin have been reported to be involved in the pathogenesis of diabetes-induced embryopathy [24,38,[44][45][46]. Especially, the excess of ROS is thought to be particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Although several teratogenic factors such as sorbitol accumulation [51], myo-inositol deficiency [19], arachidonic acid deficiency [18], altered prostaglandin metabolism [52] and increased concentration of 3-deoxyglucosone [53] are altered in embryos of diabetic pregnancy, the mechanisms by which these abnormalities lead to dysmorphogenesis have not been determined. Only recently, it has been shown that oxidative stress induced by maternal diabetes could lead to neural tube defects by impairing the expression of genes that control developmental processes [23].…”
Section: Discussionmentioning
confidence: 99%
“…abolic abnormalities including increased superoxide dismutase activity [15,16,17], reduced concentrations of myoinositol and arachidonic acid [18,19] and inhibition of the pentose phosphate shunt pathway [20]. Moreover, the frequency of embryonic malformations in diabetic pregnancy has been reported to be reduced by dietary supplements of antioxidants such as vitamin E or vitamin C [16,21,22,23] and butylated hydroxytoluene [24], suggesting that oxidative stress is involved in embryonic dysmorphogenesis.…”
mentioning
confidence: 99%
“…For example, sorbitol formation is enhanced in embryos sub- jected to a diabetic environment in vivo (52) and in vitro (53). However, attempts to block dysmorphogenesis by inhibiting aldose reductase have not been particularly successful (52)(53)(54). Evidence in favor of enhanced hexosamine pathway activity has been found in embryos of diabetic mice (55) as well as in the enhanced formation of the reactive glycosylating agent deoxyglucosone (56) in embryos subjected to high glucose concentration.…”
Section: Discussionmentioning
confidence: 99%